1980
DOI: 10.1083/jcb.84.2.298
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of vasoproliferative activity from mammalian retina.

Abstract: Vasoproliferative activity has been demonstrated in extracts of retinas from human, bovine, and feline sources. These retinal extracts are capable of stimulating (a) proliferation and thymidine uptake of bovine vascular endothelial cells in culture and (b) neovascularization on the chick chorioallantoic membrane. Extracts of skeletal muscle, cardiac muscle, and liver lack similar stimulatory activity. The activity is nondialyzable, stable at 56 degrees C, and inactivated at 100 degrees C. Retinal extracts stim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
76
1

Year Published

1983
1983
2003
2003

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 260 publications
(78 citation statements)
references
References 15 publications
1
76
1
Order By: Relevance
“…There are present in the retina of both kittens (16,17) and humans (1 8) potent growth factors that stimulate endothelial proliferation, migration, and angiogenesis. It would be consistent for oxygen to play an important role in affecting the release of (13), the tapered group were slowly withdrawn from oxygen over 3.5 wk (14), and the variable kittens were recovered in an incubator cycling between 8 and 43%, oxygen (14).…”
Section: Resultsmentioning
confidence: 99%
“…There are present in the retina of both kittens (16,17) and humans (1 8) potent growth factors that stimulate endothelial proliferation, migration, and angiogenesis. It would be consistent for oxygen to play an important role in affecting the release of (13), the tapered group were slowly withdrawn from oxygen over 3.5 wk (14), and the variable kittens were recovered in an incubator cycling between 8 and 43%, oxygen (14).…”
Section: Resultsmentioning
confidence: 99%
“…In vivo angiogenesis assays have shown that bFGF is a very potent angiogenic factor (Glaser et al, 1980a(Glaser et al, , 1980bWong et al, 2001). It is also increased in vitreous samples from patients with PDR (Sivalingam et al, 1990).…”
Section: Basic Fibroblast Growth Factor (Bfgf)mentioning
confidence: 99%
“…Basal culture medium was alpha minimal essential medium (GIBCO, Grand Island, N.Y.) with 20% heat-inactivated fetal bovine serum (HyClone Laboratories, Logan, Utah), 100 g of heparin (Sigma) per ml, 50 U of penicillin per ml, and 50 g of streptomycin per ml (defined as complete medium [CM]). HUVEC were suspended at a concentration of 10 3 /ml in CM supplemented with 10 l of bovine retinal extract per ml (CM-BRE) prepared as described previously (7,29). HUVEC were seeded in culture dishes (6-cm diameter; Falcon; Becton Dickinson Labware, Oxnard, Calif.) coated with human fibronectin (1 g/cm 2 ) and incubated at 37°C in humidified 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%